Correlating in situ RHEED and XRD to study growth dynamics of polytypism in nanowires. Issue 30 (23rd July 2021) - Jakob, Julian; Schroth, Philipp; Feigl, Ludwig; Al Humaidi, Mahmoud; Al Hassan, Ali; Davtyan, Arman; Hauck, Daniel; Pietsch, Ullrich; Baumbach, Tilo
Abstract : Time-resolved in situ RHEED and XRD during nanowire growth for determination of shape and crystal structure evolution. Abstract : Design of novel nanowire (NW) based semiconductor devices requires deep understanding and technological control of NW growth. Therefore, quantitative feedback over the structure evolution of the NW ensemble during growth is highly desirable. We analyse and compare the methodical potential of reflection high-energy electron diffraction (RHEED) and X-ray diffraction reciprocal space imaging (XRD) for in situ growth characterization during molecular-beam epitaxy (MBE). Simultaneously recorded in situ RHEED and in situ XRD intensities show strongly differing temporal behaviour and provide evidence of the highly complementary information value of both diffraction techniques. Exploiting the complementarity by a correlative data analysis presently offers the most comprehensive experimental access to the growth dynamics of statistical NW ensembles under standard MBE growth conditions. In particular, the combination of RHEED and XRD allows for translating quantitatively the time-resolved information into a height-resolved information on the crystalline structure without a priori assumptions on the growth model. Furthermore, we demonstrate, how careful analysis of in situ RHEED if supported by ex situ XRD and scanning electron microscopy (SEM), all usually available at conventional MBE laboratories, can also provide highly quantitative feedback on polytypism during growth allowing validation of current vapour–liquid–solid (VLS) growth models.